Management of Antidiabetic Therapy in Patients Undergoing [18F]FDG PET - Urbano Ferreira, Helena; Canudas Costa, Mafalda; Canha , Marta; Rodrigues, Elisabete; Lemos, Maria do Sameiro; Soeiro, Paula; Faria, Maria Teresa; Queirós, Joana (Acta Médica Portuguesa, 2026)
Positron emission tomography (PET) with fluorodeoxyglucose [18F]FDG is a technique used to identify areas of increased glycolytic metabolism, aiding in the diagnosis, staging, and follow-up of neoplastic, infectious, or inflammatory disease. In people with diabetes mellitus (DM), hyperglycemia and hyperinsulinemia alter the radiotracer biodistribution, compromising the diagnostic accuracy of this test. The absence of clear guidelines may result in inadequate patient preparation and the need to postpone or repeat the test, causing harm to the patient and the institution. This clinical practice guideline results from a review of available evidence and a multidisciplinary consensus process between the Endocrinology and Nuclear Medicine services of Unidade Local de Saúde São João, aiming to establish recommendations applicable to the Portuguese hospital context. The document includes detailed recommendations on the management of antidiabetic drugs before performing [18F]FDG PET, organized by specific clinical scenarios: 1) type 2 DM; 2) type 1 DM, including patients with continuous subcutaneous insulin infusion systems; and 3) diabetes secondary to corticosteroid therapy. In case of hyperglycemia between 200 - 350 mg/dL on the day of the test, the guideline includes the administration of insulin according to a personalized scheme, adapted to body mass index and renal function. The implementation of this guideline aims to standardize the preparation of people with diabetes for [18F]FDG PET and minimize the need to postpone or repeat tests, allowing for the optimization of hospital resource management.